Higher education and employability skills: barriers and facilitators of employer engagement at local level - Suleman, F. (2021)
This research examines the barriers and facilitators to employers’ engagement with higher education institutions. The data were collected through interviews with a set of employers (n = 19) in the Northern region of Portugal, V.N.de Famalicão, in 2019. We begin by exploring employers’ engagement activities as a potential solution to address local-level skill problems. Empirical evidence suggests that the engagement activities are mostly passive as firms use higher education largely as a recruitment channel. The differences in organizational goals and culture are the most cited barriers to the lack of more active engagement. Some efforts have recently been made to strengthen the ties between higher education and employers, notably through a local multi-stakeholder partnership as a potential broker. However, it will take time for this to bear fruit and contribute to reducing skill gaps and shortages. The data show that despite employers’ apparent willingness, more effort must be made to encourage active engagement